Field report, fall 1994, Thomas Kent - Kent, Thomas H. (Thomas Hugh), 1934-et al (1994)
An annotated list of birds sighted by Thomas Kent. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1994. Plustek - flatbed